The World Price of Foreign Exchange Risk. - Dumas, Bernard; Solnik, Bruno (Journal of Finance, 1995)
Departures from purchasing power parity imply that different countries have different prices for goods when a common numeraire is used. Stochastic changes in exchange rates are associated with changes in these prices and constitute additional sources of risk in asset pricing models. This article investigates whether exchange rate risks are priced in international asset markets using a conditional approach that allows for time variation in the rewards for exchange rate risk. The results for equities and currencies of the world's four largest equity markets support the existence of foreign exchange risk premia.